2007
DOI: 10.1017/s0954579407000363
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral inhibition and anxiety disorders: Multiple levels of a resilience process

Abstract: Behavioral inhibition is reported to be one of the most stable temperamental characteristics in childhood. However, there is also evidence for discontinuity of this trait, with infants and toddlers who were extremely inhibited displaying less withdrawn social behavior as school-age children or adolescents. There are many possible explanations for the discontinuity in this temperament over time. They include the development of adaptive attention and regulatory skills, the influence of particular styles of paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
298
2
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 343 publications
(329 citation statements)
references
References 120 publications
22
298
2
4
Order By: Relevance
“…Thus, it is argued that that enhanced amygdala activation to novelty and activation of "fear" circuitry may underlie not only infant negative reactivity to novelty, but also BI and preschool social reticence (Degnan & Fox 2007, Kagan et al 1988. In support of these conjectures, McManis and colleagues (2002) have reported that children who were emotionally reactive at 4 months and who displayed high levels of BI at ages 14 and 21 months were likely to demonstrate right frontal electroencephalogram (EEG) asymmetries in late childhood.…”
Section: The Developmental Course Of Childhood Social Withdrawal Biolmentioning
confidence: 99%
“…Thus, it is argued that that enhanced amygdala activation to novelty and activation of "fear" circuitry may underlie not only infant negative reactivity to novelty, but also BI and preschool social reticence (Degnan & Fox 2007, Kagan et al 1988. In support of these conjectures, McManis and colleagues (2002) have reported that children who were emotionally reactive at 4 months and who displayed high levels of BI at ages 14 and 21 months were likely to demonstrate right frontal electroencephalogram (EEG) asymmetries in late childhood.…”
Section: The Developmental Course Of Childhood Social Withdrawal Biolmentioning
confidence: 99%
“…Asimismo, estos resultados sugieren que una intervención para incrementar las emociones positivas también puede estar indicada para problemas de ansiedad, ya que la sensibilidad al castigo es un elemento clave en la activación del sistema de alarma, y los rasgos de inhibición en la personalidad están asociados al desarrollo de trastornos de ansiedad (e.g., Degnan y Fox, 2007). ¿En qué casos podría no estar indicado?…”
Section: Límites De Las Intervenciones Positivasunclassified
“…189 This is a general overview about pediatric anxiety disorders. More specific and comprehensive reviews about the following topics can be found in the literature: prevalence, 15,[18][19][20] behavioral inhibition, [190][191][192] behavioral genetics, 48,52 genetics, 55,56,193,194 gene vs. environment interplay, 52,70 pathophysiology, 31,71 neural substrates, 71 normal development of fears, 195 psychopharmacological treatment, [196][197][198] and CBT. 164,[199][200][201] Conclusions Anxiety disorders are prevalent, associated with a number of negative life outcomes, and currently underrecognized and under-treated.…”
Section: Preschool Children Treatment and Preventionmentioning
confidence: 99%